5 CLARYS: clinical assessment of WEB® device in ruptured aneurysms: 1-month clinical results. (July 2018) - Spelle, L; Herbreteau, D; Narata, A; Bibi, R; Ikka, L; Mihalea, C; Caroff, J; Moret, J; Barreau, X; Ferre, J; Gauvrit, J; Raoult, H; et al.
Abstract : Introduction: The intrasaccular flow diversion device WEB is a system used in the treatment of wide necked bifurcation aneurysm. The large number of clinical studies conducted have included mainly unruptured aneurysms. The CLARYS study has been set up to evaluate the efficacy and the safety of the WEB system used to treat bifurcation ruptured aneurysms. Materials and methods: The CLARYS study is a prospective, multicenter evaluation conducted in 13 interventional neuroradiological departments in France and Germany. The study design meets the Good Clinical Practice (GCP) standards with data collected in an eDC 100% monitored and endpoints independently evaluated. The primary endpoint is defined as the re-bleeding rate at 1 month post procedure. The secondary endpoints are the rate of adverse events related to the device, the procedure or the disease, the neurological evaluation at 1 month and 1 year based on mRS, the occlusion at 1 year based on the WEB Occlusion Scale (WOS) and the procedure and fluoroscopy time. Results: From February 2016 to September 2017, 60 patients (women: 31, 51.7%; mean age: 54.5±1.49 years) with 60 aneurysms were included in the study. The aneurysms locations were at the anterior communicating artery (26/60, 43.3%), the middle cerebral artery bifurcation (23/60, 38.3%), the basilar apex (7/60, 11.7%), the anterior cerebral artery (2/60, 3.3%), the internal carotid artery terminus (1/60, 1.7%) and the posterior communicating artery (1/60, 1.7%). The WEB device was successfully implanted in 56/60 cases (95.0%) The adverse events reported by the sites and adjudicated by the Clinical Event Adjudicator (CEA) were described based on timeline occurrence (per procedure or post procedure), category of events, clinical impact and relationship to device, procedure or disease. The primary endpoint will be presented as well as the morbidity and mortality at 1 month. The 12 months data are under collection so will not be available. Conclusion: The study results at 1 month will be presented to address the rate of re bleeding and the safety of the device used in the treatment of ruptured bifurcation aneurysm, following clinical evaluation conducted according to study GCP. Disclosures: D. Herbreteau: 2; C; MicroVention. A. Narata: None. R. Bibi: None. L. Ikka: None. C. Mihalea: None. J. Caroff: None. J. Moret: 2; C; MicroVention, Medtronic, Balt. 4; C; Sensome. X. Barreau: None. J. Ferre: None. J. Gauvrit: None. H. Raoult: None. J. Fiehler: 1; C; German Ministry of Science and Education (BMBF), German Ministry of Economy and Innovation (BMWi), German Research Foundation (DFG), European Union (EU), Hamburgische Investitions-und Forderbank (IFB), Medtronic, MicroVention, Philips, Stryker. 2; C; Acandis, Boehringer Ingelheim, Cerenovus, Covidien, Medtronic, Medina, MicroVention, Penumbra, Route 92, Stryker. J. Buhk: 2; C; Sequent, MicroVention. V. Costalat: 2; C; Medtronic, Stryker, Balt, Cerenovus, MicroVention. A. Januel: None. C. Cognard: 2; C; Stryker, MicroVention, Medtronic, Cerenovus. T. Liebig: None. M. Bester: None. H. Desal: None. B. Daumas-Duport: None. R. Bourcier: None. M. Mohlenbruch: None. J. Berkefeld: 2; C; Sequent/MicroVention. R. Du Mesnil de Rochemont: 2; C; Sequent. W. Weber: 2; C; Phenox, MicroVention, Medtronic, Penumbra, Stryker. S. Velasco: None. A. Biondi: None. J. Byrne: 2; C; Oxford Endovascular Ltd. L. Pierot: 2; C; Balt, Cerus Endovascular, MicroVention/Sequent, Phenox, Vesalio, Penumbra.